Optimal Second Order Integral Sliding Mode Based Composite Nonlinear Feedback Approach for an Electrostatic Micromirror - Hui Chen (IEEE, 2020)
In this article, an optimal second order integral sliding mode based composite nonlinear feedback (SOISM-CNF) controller is presented for an electrostatic micromirror. The proposed controller is able to improve the transient performance and guarantee robustness against uncertainties simultaneously. A tabu search and particle swarm optimization (TS-PSO) algorithm is used to solve the parameter tuning problem. The input saturation issue is considered in the SOISM-CNF controller design. The stability of closed-loop system is proved by Lyapunov stability theory. The simulation results demonstrate the effectiveness of SOISM-CNF controller with guaranteed transient performance under the external disturbances.